2023
DOI: 10.1126/science.adi9601
|View full text |Cite
|
Sign up to set email alerts
|

Large effective magnetic fields from chiral phonons in rare-earth halides

Jiaming Luo,
Tong Lin,
Junjie Zhang
et al.

Abstract: Time-reversal symmetry (TRS) is pivotal for materials’ optical, magnetic, topological, and transport properties. Chiral phonons, characterized by atoms rotating unidirectionally around their equilibrium positions, generate dynamic lattice structures that break TRS. Here, we report that coherent chiral phonons, driven by circularly polarized terahertz light pulses, polarize the paramagnetic spins in cerium fluoride in a manner similar to that of a quasi-static magnetic field on the order of 1 tesla. Through tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…Through first-principles calculations and phenomenological theories, researchers have found that this system exhibits chiral phonons capable of generating a significant magnetic effect, 45 which has been experimentally observed. 35 Additionally, the introduction of a magnetic field has been discovered to induce an abnormal large band splitting, which is several orders of magnitude greater than the result predicted by the previous phonon Zeeman effect, thus demonstrating a quite novel phenomenon (Figure 5(b)). These novel effects induced by chiral phonons provide a new approach to magnetic control through nonmagnetic materials.…”
Section: ■ Applications Of Chiral Phononsmentioning
confidence: 80%
See 1 more Smart Citation
“…Through first-principles calculations and phenomenological theories, researchers have found that this system exhibits chiral phonons capable of generating a significant magnetic effect, 45 which has been experimentally observed. 35 Additionally, the introduction of a magnetic field has been discovered to induce an abnormal large band splitting, which is several orders of magnitude greater than the result predicted by the previous phonon Zeeman effect, thus demonstrating a quite novel phenomenon (Figure 5(b)). These novel effects induced by chiral phonons provide a new approach to magnetic control through nonmagnetic materials.…”
Section: ■ Applications Of Chiral Phononsmentioning
confidence: 80%
“…More importantly, the converted phonons were confirmed to possess chirality . Similarly, regarding the ultrafast demagnetization of magnetic materials, researchers have found that the lost spin AM in the spin system is transferred to the lattice on a femtosecond time scale. With this unique mechanism and interesting AM conversion process, an outstanding and natural idea is whether the AM information in a spin system can be controlled through lattice dynamics. An interesting endeavor involves the surface acoustic wave (SAW) experiment, which demonstrates that the AM of elastic wave can achieve magnetization control of ferromagnetic thin films by means of the phononic-to-electronic conversion of AM, as shown in Figure (a) .…”
Section: Applications Of Chiral Phononsmentioning
confidence: 99%
“… 1 When more than one type of carriers, such as electrons and phonons, are present in the system, topological or band geometric information of electrons can be transferred to phonons through some specific form of electron-phonon coupling. This could significantly change the phonon physics and give rise to various intriguing properties of phonons, such as giant phonon orbital magnetic moment, 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 phonon Hall viscosity, 10 phonon rotoelectric effect, 11 phonon magnetochiral effect, 12 , 13 phonon helicity, 14 , 15 phonon dichroism, 16 , 17 , 18 etc.…”
Section: Introductionmentioning
confidence: 99%
“…At the non-resonant condition the phonon mode largely preserves its characteristics, whereas the mixture with magnon component produces a sizable magnetic moment of the phonon [11]. The intrinsic and optical-driven chiral phonon modes impose an effective magnetic field to spins [12,13].…”
Section: Introductionmentioning
confidence: 99%